Analisis komparatif aplikasi video conference terhadap kualitas jaringan nirkabel kampus berdasarkan variabel QoS - Pratama, Mohammad Aditya Alvin; Ilmananda, Asri Samsiar (Universitas Merdeka Malang, 2024)
The quality of the Wi-Fi network is very important in supporting the increasing use of video conferencing applications in educational environments. This research aims to analyze the comparative quality of Wi-Fi networks in campus environments in video conference applications based on the Quality of service (QoS) variable. Research was conducted on three video conferencing applications, namely Zoom, Google Meet, and Jitsi. Network quality is measured from four QoS variables including throughput, delay, packet loss, and jitter. The research results show that the application that runs best on the campus wireless network is Google Meet, with the highest average index among the other applications tested, namely 3.91 or Excellent. It is hoped that this research will provide useful guidance for educational institutions to improve video conferencing services, as well as ensure that students and staff can communicate remotely effectively without significant obstacles due to Wi-Fi network quality problems. With a better understanding of network quality and application needs, institutions can make improvements to network infrastructure and provide recommendations for selecting video conferencing applications that suit existing network conditions.